‘Alâqatu istî’âbu mufrodâti mâdatu al muthâla’ati ‘alâ al insyâi al ‘arabi li thâlibâti al fashli al khâmisi bikuliyyati al mu‘allimât al islâmiyyah dârussalâm gontor li al banât - Yoke Suryadarma; Lutfia Hanif Anadhofi (At-Ta'dib, 2018)
Arabic is one element of the success of female students in learning. Therefore, they are required to learn Arabic as well as possible and with all their efforts. Darussalam Islamic boarding school for female 1 (GP1) is well-known as the famous institute  with Arabic and English learning. All students who are in it, learn both languages from academic activities in the classroom and outside the classroom with very complete Arabic material. These materials are very helpful l for them in mastering Arabic. One of these materials is Mutholaah and Insya’ Tahriri. In this paper, the author wants to uncover and answer the question, is there a relationship between mastering Mutholaah and Insya’ Tahriri ?. In order to answer this question, the author uses quantitative methods and makes the test and writing documentation an instrument in collecting data and the use of formulas related to this problem in order to arrive at the results and conclusions.